Genetic analyses of the bidirectional associations between common mental disorders and asthma - Yan, Zian; Chen, Jingjing; Guo, Lijun; Zhang, Hongwei; Ding, Yanqiu; Ren, Gaocan; Mao, Yiyi; Bai, Ruina; Ma, Xiaochang (Frontiers in Psychiatry, 2024)
Objective Although extensive research has explored the link between mental disorders and asthma, the characteristics and patterns of this association are still unclear. Our study aims to examine the genetic causal links between common mental disorders (specifically, anxiety and depression) and asthma. Methods We conducted genetic analyses including linkage disequilibrium score regression (LDSC) and bidirectional two-sample Mendelian randomization (MR) analyses, and utilized summary statistics from recent large-scale Genome-Wide Association Studies (GWASs) in European populations, covering sensation of anxiety or depression, anxiety sensation, depression sensation, anxiety disorders, major depression disorder (MDD), and asthma. Results LDSC revealed significant genetic correlations among sensation of anxiety or depression, MDD and asthma (P < 0.017), highlighting potential genetic correlation between anxiety disorders and asthma (P < 0.05 yet > 0.017). In bidirectional two-sample MR, inverse-variance weighted (IVW) analyses suggested that genetic liability to asthma was significantly associated with an increased risk of sensation of anxiety or depression (OR = 4.760, 95%CI: 1.645–13.777), and MDD (OR = 1.658, 95%CI: 1.477–1.860). Conversely, IVW analyses indicated that genetic liability to anxiety disorders was not associated with an increased risk of asthma (P > 0.01), nor was genetic liability to asthma associated with an increased risk of anxiety disorders (P > 0.01). Furthermore, no significant genetic causal relationships were observed for other studied traits. Multivariate MR, after adjusting for body mass index and alcohol consumption, further corroborated the independent causal effect of genetic predisposition to MDD on the risk of asthma (OR = 1.460, 95% CI: 1.285–1.660). Conclusion Our study establishes MDD as a predisposing factor for asthma. Meanwhile, anxiety disorders are not causal risk factors for asthma, nor is the reverse true. It is recommended to closely monitor asthma symptoms in patients with MDD.